KUALITAS LAYANAN, KESADARAN MEREK, DAN ANALISIS PENGARUH MENGHORMATI KEPUTUSAN UNTUK MENGGUNAKAN LAYANAN PERBANKAN SYARIAH (STUDI KASUS NASABAH BANK MUAMALAT INDONESIA - M Guffar Harahap; Veri Pramudia; Rahmadani Rahmadani (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
All religious communities around the world support the current Islamic banking system. The first Islamic bank in Indonesia is Bank Muamalat Indonesia. Bank Muamalat Indonesia has made various efforts to attract potential customers to use its services, such as offering a variety of services that can help them conduct financial transactions. However, despite having a wide range of services, Bank Muamalat Indonesia is still unable to compete in the Islamic savings market. This research aims to develop a conceptual model to explain how service quality, brand awareness, and religiosity can influence purchasing decisions. Previous research also found inconsistent results between service quality, brand awareness, and religiosity on purchase decisions made to Bank Muamalat Indonesia Semarang City customers. This research involved 104 respondents who were customers of Bank Muamalat Indonesia who lived in Semarang City. Data was collected through questionnaire methods that were shared online and offline. Next, the data was analyzed quantitatively using Multiple Linear Regression Analysis. This is done using the SPSS program version 24. The results showed that religiosity, brand awareness, and service quality have a good and significant influence on consumers' decisions to buy something. In addition, the study found that religiosity has the most influence on consumers' decisions to buy something. Therefore, all hypotheses related to this study are recognized.